Work Women Did to Make Constitutional Rights Work for Women - Ruth, Nancy (Atlantis, 2015)
Women were mobilizing in anticipation of constitutional reform in 1980 and secured a first round of significant amendments to section 15 equality rights by January 1981. The final Constitution Act, 1982 placed a three-year moratorium on section 15. Governments needed time to adjust their legislation to the equality requirements. Activist Nancy Ruth reflects on what the women’s movement did during those three years to create a rights framework that would work for women. She sets forth six major initiatives that have not been incorporated into the historical record. She concludes by assessing the strengths and weaknesses of this period of activism for women’s equality.